Powdered Oil Palm (Elaesis guineensis Jacq) Leaf as Remedy for Hydrocarbon induced Liver Damage in Rats - Achuba, F. I. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Humans are faced with a number of diseases and chemical toxicity due to sustained pollution of environment. One of the management strategies adopted in recent times is the use of herbs. This is the driving force for this study. Ninety six female rats were mobilized for this study and were divided into six groups of sixteen rats each. Rats in group A served as control and were fed with diet devoid of any treatment while rats in groups B and C were fed with diets treated with varying amounts of ground Elaesis guineensis leaf. Rats in group D were fed with hydrocarbon adulterated diet. Rats in groups E and F were fed with adulterated diet mixed with the same amounts of ground Elaesis guineensis leaf as in groups B and C. Oxidative stress indicators and histological analysis were carried out on the rat’s liver after exposure period of three and six months respectively. The results show that pretreatment of hydrocarbon adulterated diet with Elaesis guineensis leaf normalized values of lipid peroxidation (LP), superoxide dismutase activity (SOD), catalase activity (CAT) and xanthine oxidase activity (XO) relative to control values. Histological analyses indicate protective influence of Elaesis guineensis leaf against harmful consequence of hydrocarbon on the liver. It is apparent that the leaves of Elaesis guineensis could be used in the management of hydrocarbon linked liver damage.